Tanzania : 2004 Article IV Consultation and Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; Staff Statement; and Public Information Notice and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2004)
This paper examines Tanzania's 2004 Article IV Consultation and Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. Tanzania has continued to maintain macroeconomic stability and to make substantial progress in structural reform. Real GDP growth has been strong, averaging almost 6 percent during the past three years, and is increasingly driven by improvements in total factor productivity. High growth reflected both the continued strong performance in the manufacturing, mining, and construction sectors, as well as the solid growth in the agricultural sector.